Characterization of human serum albumin's interactions with safranal and crocin using multi-spectroscopic and molecular docking techniques - Salem, Alaa A. (Biochem Biophys Rep, 2019)
Interaction mechanisms of human serum albumin (HSA) with safranal and crocin were studied using UV–Vis absorption, fluorescence quenching and circular dichroism (CD) spectroscopies as well as molecular docking techniques. Changes in absorbance and fluorescence of HSA upon interactions with both compounds were attributed to their binding to amino acid chromophores located in subdomains IIA and IIIA. Fluorescence secondary inner filter effect was excluded using 278 nm and 340 nm as the wavelengths of HSA's excitation and fluorescence while safranal and crocin absorbed at 320 nm and 445 nm, respectively. Stern-Volmer model revealed a static quenching mechanism involve the formation of non-fluorescent ground state complexes. Stern-Volmer, Hill, Benesi-Hilbrand and Scatchard models gave apparent binding constants ranged in 4.25 × 10(3) - 2.15 × 10(5) for safranal and 7.67 × 10(3) - 4.23 × 10(5) L mol(−1) for crocin. CD measurements indicated that 13 folds of safranal and crocin unfolded the α-helix structure of HSA by 7.47–21.20%. In-silico molecular docking revealed selective exothermic binding of safranal on eight binding sites with binding energies ranged in −3.969 to −6.6.913 kcal/mol. Crocin exothermally bound to a new large pocket located on subdomain IIA (sudlow 1) with binding energy of −12.922 kcal/mol. These results confirmed the formation of HSA stable complexes with safranal and crocin and contributed to our understanding for their binding characteristics (affinities, sites, modes, forces … etc.) and structural changes upon interactions. They also proved that HSA can solubilize and transport both compounds in blood to target tissues. The results are of high importance in determining the pharmacological properties of the two phytochemical compounds and for their future developments as anticancer, antispasmodic, antidepressant or aphrodisiac therapeutic agents.